2019
DOI: 10.1111/jcmm.14695
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics‐based screening of the target proteins associated with antidepressant‐like effect and mechanism of Saikosaponin A

Abstract: Depression is a commonly occurring neuropsychiatric disease with an increasing incidence rate. Saikosaponin A (SA), a major bioactive component extracted from Radix Bupleuri, possesses anti‐malignant cell proliferation, anti‐inflammation, anti‐oxidation and liver protective effects. However, few studies have investigated SA’s antidepressant effects and pharmacological mechanisms of action. Our study aimed to explore the anti‐depression effect of SA and screen the target proteins regulated by SA in a rat model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…One such approach was that of the isobaric tag for relative and absolute quantification (iTRAQ) quantitative technique. A latest study using an iTRAQ‐based method suggested the proline‐rich transmembrane protein 2 played a crucial role in rat model of chronic unpredictable mild stress (CUMS) with saikosaponin A treatment and provided novel candidate target of the anti‐depression mechanism of saikosaponin A (Guo et al., 2020). In addition, another study also identified rapamycin protein kinase (mTOR) signalling as an important target of panduratin A by iTRAQ proteomic analysis (Lai et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One such approach was that of the isobaric tag for relative and absolute quantification (iTRAQ) quantitative technique. A latest study using an iTRAQ‐based method suggested the proline‐rich transmembrane protein 2 played a crucial role in rat model of chronic unpredictable mild stress (CUMS) with saikosaponin A treatment and provided novel candidate target of the anti‐depression mechanism of saikosaponin A (Guo et al., 2020). In addition, another study also identified rapamycin protein kinase (mTOR) signalling as an important target of panduratin A by iTRAQ proteomic analysis (Lai et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rosmarinic acid can treat neurodegenerative diseases via anti-neuroinflammatory activity ( Wei et al, 2018 ). Furthermore, saponins, such as saikosaponin A, are the major bioactive component extracted from Radix Bupleuri ( Chen et al, 2018 ; Liu R et al, 2018 ) and have anti-inflammatory and antioxidant pharmacological activities, as well as a good therapeutic effect on many diseases of the central nervous system and cardiovascular system ( Guo et al, 2020 ). Flavonoids, such as hesperidin and hesperetin, can inhibit inflammatory reactions and oxidative stress, and protect nerve cells and vascular endothelium ( Hwang et al, 2012 ; Van Rymenant et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have con rmed that abnormal ribosomal proteins expression or transcription exists in patients with depression and animal models. Most of such studies have observed that the expression of ribosomal proteins is up-regulated or increased transcription in blood, liver, hippocampus and other tissues of depressed individuals [23][24][25]. It has been also observed that the expression of ribosomal proteins in the hippocampus of rats was signi cantly down-regulated under 3-week exposure to CUMS [26].…”
Section: Discussionmentioning
confidence: 99%